Altered microglial phagocytosis in GPR34‐deficient mice. Issue 2 (20th August 2014) - Preissler, Julia; Grosche, Antje; Lede, Vera; Le Duc, Diana; Krügel, Katja; Matyash, Vitali; Szulzewsky, Frank; Kallendrusch, Sonja; Immig, Kerstin; Kettenmann, Helmut; Bechmann, Ingo; Schöneberg, Torsten; et al.
<x xml:space="preserve">Abstract</x> GPR34 is a Gi/o protein‐coupled receptor (GPCR) of the nucleotide receptor P2Y12‐like group. This receptor is highly expressed in microglia, however, the functional relevance of GPR34 in these glial cells is unknown. Previous results suggested an impaired immune response in GPR34‐deficient mice infected with Cryptococcus neoformans. Here we show that GPR34 deficiency results in morphological changes in retinal and cortical microglia. RNA sequencing analysis of microglia revealed a number of differentially expressed transcripts involved in cell motility and phagocytosis. We found no differences in microglial motility after entorhinal cortex lesion and in response to laser lesion. However, GPR34‐deficient microglia showed reduced phagocytosis activity in both retina and acutely isolated cortical slices. Our study identifies GPR34 as an important signaling component controlling microglial function, morphology and phagocytosis. GLIA 2015;63:206–215